Safety and Delivery Selection Analysis at Sanctoo Suites & Villas Singapadu - Pancane, Iwayan Dikse; Supranartha, Agus (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research focuses on analyzing the types of conductors and electrical installation safety at Sanctoo Suites & Villas Singapadu, where this research aims to determine the type of conductor, current carrying strength (CRC) flowing in the conductor, protection MCB, contactor, TOR, ELCB, and Surge Arrester installed already meets PUIL standards.After this research is completed, it is hoped that this research can provide consideration to the company that the importance of the electrical installation system, especially the installation of electric power for safety and comfort, by using the installation of electrical equipment according to standards.